An Examination of the Conceptual Structure of Long-Term Goal Striving. (April 2022) - Lam, Kelly Ka Lai; Zhou, Mingming
Long-term goal striving has been recognized as an important stage in goal achievement. Compared with the development of measurements of goal setting, researchers tended to measure goal striving in different manners. This study examined the conceptual structure of goal striving and validated a new scale to operationalize the construct within academic learning contexts. A 25-item scale was validated with 522 Chinese university students to assess its factor structure, reliability, gender invariance, criterion-related validity, and incremental validity. Confirmatory factor analysis results supported both the first-order and second-order model. Overall, the scale showed good reliability, validity, and invariance across gender. We suggested that this new scale could be used as an effective measure to assess the level of goal striving among university students in a Chinese context.